The life of crime: detecting the history of mysteries and their creators - Edwards, Martin (Collins Crime Club, 2022)
In the first major history of crime fiction in fifty years, The Life of Crime: Detecting the History of Mysteries and their Creators traces the evolution of the genre from the eighteenth century to the present, offering brand-new perspective on the world's most popular form of fiction.